Design and Experimental Analysis of a Cascaded Voltage Multiplier for High Voltage Testing - Radhika, Goru; M. Suryakalavathi, Dr.; Rohith kumar, D. (International Journal of Engineering and Technology, 2018)
This paper highlights the details of the Voltage Multiplier circuit and expresses the technical aspects of the circuit in detail. This circuit has the capability to produce a 12kV High Voltage DC output from a conventional 230-volt AC supply. This circuit is essentially a Cascaded Voltage Multiplier, designed to multiply the output by 8 times the input voltage from the power supply in series with a step-up transformer. The circuit can generate energy in the range of kilo joules which can be used for the testing of high voltage equipment.Â Â  Â